Low Frequency of Asymptomatic and Submicroscopic Plasmodial Infections in Urabá Region in Colombia (2018)
ABSTRACT: Background. A screening for malaria parasites was conducted with asymptomatic residents in Colombia. Methods. A descriptive study was carried out in December 2012 in four municipalities of Urabá region in Colombia. A convenience sample of 400 subjects was selected. Participants responded to a survey regarding epidemiological data and blood samples were taken from capillary blood obtained by finger prick for thick smear, rapid diagnostic test (RDT), and polymerase chain reaction (PCR). Results. 399 subjects aged 0.2-98 years were studied (median 22; 221 female (55%)). Episodes of malaria in the last year confirmed by thick film were reported by 47 participants (12%). In 399 samples tested by RDT 4 (1%) were positive (1 with P. falciparum, 3 with P. vivax), and 3 were confirmed by PCR. In 399 thick blood smears examined 5 (1.3%) were positive (2 with P. falciparum, 3 with P. vivax), and 3 were confirmed by PCR. In 227 samples, PCR showed 6 (2.6%) positive samples. The parasitaemia was below 1,440 parasites/μL. The best agreement between diagnoses was found between the RDT and thick blood smears (Kappa = 0.75). Conclusion. Plasmodial afebrile infection was found in 2% of the studied population, by three diagnostic methods, in residents from a low endemic malaria region in Colombia.